Superhard alloy material

By alloying WC-Fe carbide alloys with chromium to expand the phase diagram, the challenges of producing dense, phase-pure WC-Fe alloys for fusion reactors are addressed, resulting in alloys with enhanced mechanical properties and reduced radioactivity.

JP2025512820AActive Publication Date: 2025-04-22ELEMENT SIX GMBH

Patent Information

Application Number
JP2024556798
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-14
Publication Date
2025-04-22
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

The production of 100% dense WC-Fe carbide alloys for fusion reactor walls is challenging due to the narrow two-phase region of iron-based binders and carbide alloys, leading to the formation of brittle phases like η phase or free carbon.

Method used

Alloying the binder phase with chromium expands the W-C-Fe phase diagram, allowing for the production of WC-Fe carbide alloys without η phase or free carbon inclusions, by dissolving Cr, W, and C in a Fe-based binder matrix.

Benefits of technology

This approach enables the manufacture of completely dense WC-Fe carbide alloys with improved hardness and fracture toughness, suitable for neutron shielding in fusion reactors, while avoiding radioactive cobalt and minimizing the presence of brittle phases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512820000001_ABST
    Figure 2025512820000001_ABST
Patent Text Reader

Abstract

A cemented carbide body for neutron shielding and a method for producing the same, characterized in that the cemented carbide body contains WC, Fe, and Cr, the Cr being present in an amount of about 1% by mass to about 150% by mass relative to the Fe content, and the cemented carbide body contains WC grains, cementite grains, and dissolved Cr, W, and C in an Fe-based binder matrix material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to hardmetal materials and blocks including same. [Background technology]

[0002] Fusion reactors for fusion power plants, currently under intensive development, require protective materials against the intense neutron radiation caused by the fusion process in extremely hot plasma. As a result, the high-energy neutrons emitted from the plasma must be slowed (moderated) and captured (absorbed) by the containment walls surrounding the plasma. The most suitable material for this is known to be tungsten carbide (WC). However, it is not possible to produce 100% dense blocks for the reactor walls from pure tungsten carbide without metal binders. Furthermore, porosity in the wall material must be avoided.

[0003] Traditionally, cobalt (Co)-based binders are employed in the manufacture of hard metals, but according to MR Gilbert, T. Eade et al (Waste implications from minor impurities in European DEMO materials. Nuclear Fusion, April 2019, DOI: 10.1088 / 1741-4326 / ab154e), the use of conventional WC-Co hard metals required for neutron shielding is problematic because cobalt remains radioactive for a long time. According to the same paper, iron is a significantly better binder material in terms of the lifetime of its radioisotopes, so WC-Fe hard metals are preferred for the manufacture of blocks that form the reactor walls required for neutron shielding. However, as is well known (see, for example, B. Uhrenius, H. Pastor, E. Pauty, On the composition of Fe-Ni-Co-WC-based cemented carbides, Int. J Refractory Met Hard Mater. 15(1997)139-149), the two-phase region of the iron-based binder and the cemented carbide at 1000°C, i.e., the region where only the carbide phase and the binder phase coexist in equilibrium, is very narrow (on the order of 0.01% by mass or less), which is more than 10 times lower than that of conventional WC-Co cemented carbides. This poses great difficulties in the production of cemented carbides with iron as the binder, because even the slightest deviations in the carbon content in the initial WC-Fe classified powder and the carbon content in the sintering furnace atmosphere lead to the formation of η-phase or free carbon, which are very brittle. Therefore, WC-Fe cemented carbides are not produced in the cemented carbide industry. This is because it is virtually impossible to manufacture cemented carbide without inclusions of eta phase and free carbon, which make the cemented carbide very brittle and unacceptable for the manufacture and brazing of the aforementioned blocks for the fusion reactor walls. Summary of the Invention [Problem to be solved by the invention]

[0004] The main object of the present invention is to overcome the above mentioned difficulties. [Means for solving the problem]

[0005] The object of the present invention is achieved by alloying the binder phase with a chemical element that remains radioactive for a relatively short time. It has surprisingly been found that, as described herein, by adding powders of different chemical elements, in particular chromium, in specific amounts to the WC-Fe classified powder, it is possible to expand the region of the WC-Fe phase diagram in which only carbide phases, i.e. WC and cementite, and a metallic binder, i.e. an Fe-based binder, exist in equilibrium, thereby ensuring the possibility of manufacturing such hard metals on a production scale without major technical difficulties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Thus, in a first aspect of the present invention, there is provided a cemented carbide body for neutron shielding, said cemented carbide body containing, e.g. comprising, consisting of or essentially of WC, Fe and Cr, said Cr being present in an amount of up to 6% by weight relative to the Fe content, and wherein the microstructure of the cemented carbide body comprises, consists of or consists essentially of WC grains, cementite grains and dissolved Cr, W and C in an Fe-based binder matrix material.

[0007] In one option, the cemented carbide comprises up to 5% by weight of Si, Ti, V, Ge, Ta, Pb and / or Y, and combinations thereof, relative to the iron content.

[0008] In one option, the cemented carbide body comprises up to 50% Mn by weight relative to the Fe content.

[0009] According to a second aspect of the present invention, there is provided a cemented carbide body for neutron shielding, the cemented carbide body containing, e.g. comprising, consisting of or consisting essentially of WC, Fe and Cr, the Cr being present in an amount of about 1% to about 150% by weight relative to the Fe content, and the cemented carbide body comprising, consisting of or consisting essentially of WC grains, cementite grains and dissolved Cr, W and C in an Fe-based binder matrix material.

[0010] In one option, the Cr is present in an amount of about 1% to about 90% by weight relative to the Fe content.

[0011] In one option, the Cr is present in an amount of about 1% to about 10% by weight relative to the Fe content.

[0012] In one option, the Cr is present in an amount of about 1% to about 6% by weight relative to the Fe content.

[0013] In one option, the Cr is present in an amount of about 5% to about 90% by weight relative to the Fe content.

[0014] In one option, the Cr is present in an amount of about 5% to about 10% by weight relative to the Fe content.

[0015] In one option, the cemented carbide body has a Vickers hardness of at least 15 GPa, the Vickers hardness being measured in accordance with ISO 6507-1:2018 (Metallic materials - Vickers hardness test - Part 1: Test method).

[0016] In one option, the cemented carbide body has a Palmqvist fracture toughness of at least 7 MPa m 1 / 2 The Palmqvist fracture toughness is measured according to ISO 28079:2009 (Hardmetals - Palmqvist toughness test).

[0017] In one option, the cemented carbide body comprises less than 0.01% by weight of free carbon, where free carbon means carbon in the cemented carbide body that is present in elemental form, for example in the form of graphite.

[0018] In one option, the cemented carbide body is substantially free of free carbon.

[0019] In one option, the cemented carbide body comprises less than 0.01 wt. % eta phase.

[0020] In one option, the cemented carbide body is substantially free of eta phase.

[0021] In one option, the cemented carbide body has a porosity of less than 1%.

[0022] In one option, the cemented carbide body has a porosity of less than 0.1%.

[0023] In one option, the cemented carbide body is fully dense.

[0024] In one option, the cemented carbide body is void-free.

[0025] Characterization of porosity, carbon defects and eta-phase content is performed according to ISO 4499-4:2016 (Hardmetals - Metallographic determination of microstructure - Part 4: Characterization of porosity, carbon defects and eta-phase content).

[0026] In one option, the cemented carbide body further comprises up to 5% by weight of Si, Ti, V, Ge, Ta, Pb and / or Y, and combinations thereof, relative to the iron content.

[0027] In one option, the cemented carbide body further comprises up to 50% Mn by weight relative to the Fe content.

[0028] According to a third aspect of the present invention there is provided a method of manufacturing a cemented carbide body as described herein, the method comprising the steps of: grinding together powders of tungsten carbide, iron and chromium containing material; pressing the pulverized powder to form a compact; sintering the compact in vacuum at a temperature of not more than 1300° C. and for a time of at least 15 minutes; and Cooling the sintered body. Includes.

[0029] As an option, the method further comprises the addition of Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of a carbide, nitride, carbonitride or intermetallic compound, for example providing a milled powder comprising Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of a carbide, nitride, carbonitride or intermetallic compound at the milling stage.

[0030] According to a fourth aspect of the present invention there is provided a method of manufacturing a cemented carbide body as described herein, the method comprising the steps of: grinding together powders of tungsten carbide, iron and chromium containing material; pressing the pulverized powder to form a compact; sintering the compact in a vacuum; and Cooling the sintered body; Includes.

[0031] In one option, the sintering is carried out at a temperature of at least 1200°C.

[0032] In one option, the sintering is carried out at a temperature of up to 1300° C. and / or for a time of at least 15 minutes.

[0033] In one option, the sintering is carried out at a temperature of at most 1500°C.

[0034] In one option, the sintering is performed at a temperature of about 1250°C to about 1480°C.

[0035] In one option, the sintering is carried out for a period of at least 15 minutes.

[0036] As an option, the chromium-containing material is or includes chromium carbide or chromium nitride.

[0037] In one option, the chromium carbide is Cr3C2.

[0038] As an option, the method further comprises the addition of Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of a carbide, nitride, carbonitride or intermetallic compound, for example providing a milled powder comprising Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of a carbide, nitride, carbonitride or intermetallic compound at the milling stage.

[0039] According to a fifth aspect of the present invention there is provided a block for forming a wall of a fusion reactor, said block comprising a cemented carbide body as described herein.

[0040] According to a sixth aspect of the present invention there is provided a use of a cemented carbide body as described herein in a nuclear fusion reactor. [Brief description of the drawings]

[0041] Non-limiting examples illustrating the present disclosure will now be described with reference to the accompanying drawings, in which: [Figure 1] FIG. 1 is an optical microscope image of a cemented carbide body made according to Example 1 after etching with Murakami's reagent. [Diagram 2] FIG. 2 is an optical microscope image of the cemented carbide body made according to Example 1 after etching with Nital reagent. [Diagram 3] FIG. 3 is an optical microscope image of a cemented carbide body made according to Example 2 after etching with Murakami's reagent. [Figure 4] FIG. 4 is an optical microscope image of a cemented carbide body made according to Example 2 after etching with Nital reagent. [Diagram 5] FIG. 5 is an optical microscope image of a cemented carbide body made according to Example 3 after etching with Murakami's reagent. [Figure 6] FIG. 6 is an optical microscope image of a cemented carbide body made according to Example 3 after etching with Nital reagent. [Figure 7] FIG. 7 is an optical microscope image of a cemented carbide body made according to Example 4 after etching with Murakami's reagent. [Figure 8] FIG. 8 is an optical microscope image of a cemented carbide body made according to Example 4 after etching with Nital reagent. [Figure 9] FIG. 9 is an optical microscope image of a cemented carbide body made according to Example 5 after etching with Murakami's reagent. [Figure 10] FIG. 10 is an optical microscope image of a cemented carbide body made according to Example 5 after etching with Nital reagent. [Figure 11] FIG. 11 is an unetched high resolution scanning electron microscope image of a cemented carbide body made according to Example 5. [Figure 12] FIG. 12 is a high resolution scanning electron microscope image of the cemented carbide body produced according to Comparative Example 1 without etching. EXAMPLES

[0042] A series of experiments were performed to identify the optimum range for chromium content. The composition of the starting lab batch is shown in Table 1.

[0043] [Table 1]

[0044] Example 1 A lab batch of WC-Fe powder (10 kg) was produced by grinding together 500 g Fe, 30 g Cr3C2 powder, and 9470 g WC powder with 180 g paraffin wax in 30 kg WC-Co balls in hexane. The average particle size of the WC powder was about 6 μm. The average particle size of the Fe powder was about 3 μm and the average particle size of the Cr3C2 powder was about 2 μm. These components were ground together in a ball mill for 30 hours. The ETC (Equivalent Total Carbon) value of this mixture was approximately equal to 5.93% by mass.

[0045] After grinding, the resulting slurry was dried at a temperature of about 90°C and then sieved to obtain a graded powder suitable for pressing in a die. Cylindrical samples with a diameter of 20 mm and a height of 10 mm were pressed from this graded powder and sintered in a Sinter-HIP furnace at a temperature of 1280°C for 75 minutes (45 minutes in vacuum + 30 minutes sintering under 40 Bar Ar pressure).

[0046] As a result of sintering, a fully dense sample was obtained without any eta-phase or free carbon inclusions. The microstructure of one such sample after etching with different reagents is shown in Figures 1 and 2. As can be seen in Figure 1, the sample etched with Murakami reagent does not contain any eta-phase, and as can be seen in Figure 2, the microstructure contains some cementite, which appears as white or light grey inclusions after etching with Nital reagent. No other carbide phases besides WC and cementite were found to be present in the microstructure, indicating that the added amount of chromium carbide was completely dissolved in the binder phase during liquid phase sintering. The Vickers hardness of the sample was approximately 15.5 GPa and the Palmqvist fracture toughness was approximately 9 MPa m 1 / 2This combination of hardness and fracture toughness is close to that of conventional WC-Co hard alloys. See, for example, Roebuck B, Gee MG, Morrell R. Hardmetals - microstructural design, testing and property maps. In: Kneringer G, Roedhammer P, Wildner H, editors. Proceedings of the 15th International Plansee Seminar, Vol. 4. Reutte; 2001. p. 245-66.

[0047] Then, traces (i.e. small amounts) of the classified powder were mixed with different amounts of tungsten metal powder with an average particle size of about 0.5 μm and carbon black, so that the ETC value steadily decreased to 5.8% by mass on the one hand and increased stepwise to 6.1% by mass on the other hand, at intervals equal to 0.02% by mass C. Samples obtained from the mixtures of the classified powders thus obtained were pressed and sintered under the above conditions. Then, cross sections were made and examined for the presence of η-phase and free carbon. As a result, it was confirmed that the range of carbon content in which η-phase and free carbon are not present in the microstructure is about 0.14% by mass, which is comparable to that of conventional WC-Co cemented carbides.

[0048] Example 2 Samples were prepared as in Example 1, except that 50 g of chromium carbide powder was added and the amount of WC was reduced accordingly to make a batch of 10 kg. Sintering resulted in fully dense samples without any eta-phase or free carbon inclusions. As can be seen in Figure 3, the sample etched with Murakami's reagent does not contain any eta-phase, and as can be seen in Figure 4, the microstructure contains some cementite, which appears as white or light grey inclusions after etching with Nital's reagent. It was found that no other carbide phases besides WC and cementite were present in the microstructure, which was confirmed by XRD testing. The Vickers hardness of the sample was approximately 15.7 GPa and the Palmqvist fracture toughness was approximately 8.4 MPa m 1 / 2 This was a lower value than in Example 1.

[0049] Example 3 Samples were prepared as in Example 1, except that 80 g of chromium carbide powder was added and the amount of WC was reduced accordingly to make a 10 kg batch. Sintering resulted in a fully dense sample without any eta phase or free carbon inclusions. As can be seen in Figure 5, the sample etched with Murakami's reagent does not contain any eta phase, and as can be seen in Figure 6, the microstructure contains some cementite, which after etching with Nital's reagent appears as white or light grey inclusions. This sample is a mixture of mixed carbides (Cr,Fe) x C y The specimen also contains mixed carbide inclusions, which can be seen as dark inclusions in Figure 6 and were also confirmed by XRD testing. These mixed carbide inclusions have a dark brown color typical of Cr-Fe mixed carbides. The Vickers hardness of the specimen is approximately 15.9 GPa and the Palmqvist fracture toughness is approximately 7.6 MPa m 1 / 2 and was lower than those of Examples 1 and 2. This relatively low fracture toughness value is believed to be related to the presence of Cr-Fe mixed carbide inclusions in the microstructure.

[0050] Example 4 Samples were prepared as in Example 1, except that 150 g of chromium carbide powder was added and the amount of WC was reduced accordingly to make 10 kg batches. Sintering resulted in fully dense samples without eta-phase or free carbon inclusions. As can be seen in Figure 7, the sample etched with Murakami's reagent is free of eta-phase, and as can be seen in Figure 8, the microstructure contains a lot of cementite, which appears as white or light grey inclusions after etching with Nital's reagent. The Vickers hardness of the sample is approximately 16.5 GPa and the Palmqvist fracture toughness is approximately 7.4 MPa m 1 / 2 This was a lower value than those of Examples 1 and 2. Such a relatively low fracture toughness value is considered to be related to the fact that almost all of the Fe binder was converted to cementite.

[0051] Example 5 Samples were prepared as in Example 1, except that 500 g of chromium carbide powder was added and the amount of WC was reduced accordingly to make 10 kg batches. Sintering resulted in fully dense samples without any eta phase or free carbon inclusions. As can be seen in Figure 9, the sample etched with Murakami's reagent is free of eta phase, and as can be seen in Figure 10, the microstructure contains a lot of cementite, which appears as white or light grey inclusions after etching with Nital's reagent. Figure 11 shows an HRSEM image of the microstructure, showing that it does not contain porosity. The Vickers hardness of the sample is approximately 16.5 GPa and the Palmqvist fracture toughness is approximately 7.0 MPa m 1 / 2 , which is lower than those of Examples 1 and 2. Such a low fracture toughness value is believed to be related to the presence of Cr-Fe mixed carbide inclusions in the microstructure. Although the fracture toughness is lower than those of Examples 1 and 2, it is still high enough that the composition of Example 5 can be used to manufacture neutron shielding molded articles.

[0052] Comparative Example 1 Samples were produced as in Example 1, except that 1000 g of chromium carbide powder was added and the amount of WC was reduced accordingly to make 10 kg batches. Sintering resulted in very porous samples. The porosity was so high that it was not possible to measure the density by hydrostatic pressure methods. The fracture surface of one sample is shown in Figure 12. Such porous samples are not suitable for use in the manufacture of neutron shielding mouldings.

[0053] Comparative Example 2 Samples were produced as in Example 1, except that 5 g of chromium carbide powder was added and the amount of WC was reduced accordingly to a batch of 10 kg. Sintering resulted in a fully dense sample with inclusions of the η phase. 0.01% by weight of carbon black was added to the mixture and the sample was sintered as in Example 1. The results showed the presence of free carbon inclusions in the microstructure and that the width of the two-phase region of this alloy was equal to or close to zero, in other words, it was not possible to produce a sample without the η phase and without free carbon when using this amount of chromium. Such a material is not suitable for use in the manufacture of neutron shielding mouldings.

[0054] While the present invention has been particularly shown and described with reference to various embodiments, it will be understood by those skilled in the art that various changes in form and details can be made therein without departing from the scope of the invention as defined by the appended claims.

Claims

1. 1. A cemented carbide body for neutron shielding, the cemented carbide body comprising WC, Fe and Cr, the Cr being present in an amount of about 1% to about 150% by weight relative to the Fe content, the cemented carbide body comprising WC grains, cementite grains, and dissolved Cr, W and C in an Fe-based binder matrix material.

2. 2. The cemented carbide body of claim 1, wherein the Cr is present in an amount from about 1% to about 90% by weight relative to the Fe content.

3. 3. The cemented carbide body of claim 1 or 2, wherein the Cr is present in an amount of about 1% to about 10% by weight relative to the Fe content.

4. 4. The cemented carbide body of any one of claims 1 to 3, wherein the Cr is present in an amount of about 1% to about 6% by weight relative to the Fe content.

5. The cemented carbide body according to any one of claims 1 to 4, having a Vickers hardness of at least 15 GPa.

6. Palmqvist fracture toughness of at least 7 MPa m 1/2 The cemented carbide body according to any one of claims 1 to 5,

7. 7. The cemented carbide body of any one of claims 1 to 6, which is substantially free of free carbon.

8. 8. The cemented carbide body of claim 1, wherein the body is substantially free of eta phase.

9. 9. The cemented carbide body of claim 1, wherein the porosity of the cemented carbide body is less than 0.1%.

10. 10. The cemented carbide body of any one of claims 1 to 9, further comprising up to 5 wt.-% of Si, Ti, V, Ge, Ta, Pb and / or Y, and combinations thereof, relative to the iron content.

11. The cemented carbide body according to any one of claims 1 to 10, further comprising up to 50% by weight of Mn relative to the Fe content.

12. A method for producing a cemented carbide body according to any one of claims 1 to 11, comprising the steps of: grinding together powders of tungsten carbide, iron and chromium containing material; pressing the pulverized powder to form a compact; sintering the compact in vacuum; Cooling the sintered body. A method comprising:

13. The method of claim 12, wherein the sintering is carried out at a temperature of at least 1200°C.

14. 14. The method according to claim 12 or 13, wherein the sintering is carried out at a temperature of at most 1500°C.

15. The method of any one of claims 12 to 14, wherein the sintering is carried out at a temperature of about 1250°C to about 1480°C.

16. The method according to any one of claims 12 to 15, wherein the sintering is carried out for a period of at least 15 minutes.

17. The method according to any one of claims 12 to 16, wherein the chromium-containing material is a chromium carbide or a chromium nitride.

18. The chromium carbide is Cr 3 C 2 18. The method of claim 17, wherein:

19. 19. The method of any one of claims 12 to 18 when dependent on claim 10 or 11, further comprising adding Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of a carbide, nitride, carbonitride or intermetallic compound.

20. A block for forming a wall of a nuclear fusion reactor, characterized in that said block comprises a hardmetal body according to any one of claims 1 to 11.

21. Use of a cemented carbide body according to any one of claims 1 to 11 in a nuclear fusion reactor.

Citation Information

Patent Citations

  • Tungsten carbide-iron type sintered hard alloy and its manufacture

    JP1985208448A

  • Sintered hard alloy having wear resistance, corrosion resistance and thermal shock resistance

    JP1989119639A

  • Iron-base cemented carbide and its manufacture

    JP2001081526A

  • Oxidation resistant coating and methods of manufacturing thereof

    US20200131616A1

  • Cemented carbides comprising an fe-cr binder based metallic binder

    WO2018206174A1

Cited By

  • High-Binder-Density Cemented Carbide for Neutron Shielding Applications

    JP2025521160A

  • Low-binder, high-density cemented carbide for neutron shielding applications

    JP7887505B2